Relaxation Technique within Group Counseling to Reduce Student's Anxiety on Facing Exam: Array - Arizona Arizona; Nurlela Nurlela; Zhila Jannati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2019)
The purpose of this study is determine the effectiveness of group counseling model with relaxation technique assisted by instrumental music to reduce students' anxiety on facing exam. This type of research is quantitative with quasi-experimental research design, using the initial test design (pretest) and the final test after treatment (posttest). This research involved PGRI junior high school 1 Palembang students. The steps taken are: 1) preparation, 2) giving the pretest to the experimental group, 3) giving treatment 4), conducting posttest, and 5) the analysis of effectiveness of group counseling with relaxation techniques assisted by instrumental music to reduce the anxiety of students when facing exam. The analysis was carried out using the Wilcoxon test. Based on the results of the test, the level of students' anxiety faces the test has decreased after participating in group counseling activities with relaxation techniques. The Wilcoxon test results obtained Asymp.sig. (2-tailed) of 0.008 with 5% significance (<0.05). Therefore, it can be concluded that group counseling services with relaxation technique assisted by instrumental music is effective to reduce students' anxiety on facing exam.